Cyclic extensions of parafree groups - Wong, Peng Choon (American Mathematical Society, 1980)
Let 1 —> F —> G —> T —> 1 be a short exact sequence where F is parafree and T is infinite cyclic. We examine some properties of G when F/F' is a free Zr-module. Here F' is the commutator subgroup of F and ZT is the integral group ring of T. In particular, we show G is parafree and y„F/y„+ XF is a free Z7"-module for every n > 1 (where ynF is the nth term of the lower central series of F).